Study of Institution Model of Micro Finance to Raise Children Opportunities of Poor Families for Having Higher Education: Getting Higher Education and The Local Institutions - Khusnul Ashar; Susilo Susilo; Al Muizzuddin Fazaalloh (Institute of Research and Community Service, University of Brawijaya)
The aim of this research is for making micro financial institution that is healthy and sustainable with basic of local institution. Moreover, this research encourages the children of poor families to continue study to higher education. This research is performed within 3 years in Malang Regency. In this second year terms, the main aim of this research are : To explore more about the relation of the determinant of variables which influence the successful of poor households children to pursue study in higher education level with the existing of local economic institutions. Methodology applied in this research mainly qualitative approach. This study found that there are three main factors influencing poor households that are success to educate their children in higher education. First, the support or motivation from their children self. Second, the situation that makes children have to go to higher education. Third, the supports from their parents and family. There are three local social-economy institutions that are exist, namely: pengajian tahlil, arisan, and cooperation. The highest intensity that is followed by people sampled is pengajian tahlil and arisan. Local economy institutions that can help financial problem of poor households are arisan and brothers or family. Cooperation gets less attention from people because there is any doubtful of the people’s ability to pay installment regularly.Keywords: Micro finance institution, Poverty, Higher education